(About) experiences, mental health and coping the pandemic of university students in socio-economic vulnerability (Research, Society and Development, 2021)
The present study aims to characterize the psycho-emotional repercussions, the main stressors and the coping strategies used by university students accompanied by student assistance at a public university during the Covid-19 pandemic. In addition, we investigated the preponderant difficulties facing the changes arising from the establishment of remote education. The sample consisted of 15 students. Semi-structured interviews and thematic content analysis proposed by Bardin were used. From the interviews, 3 categories and 6 subcategories were configured. All university students presented, in different intensities, psycho-emotional repercussions after the adoption of remote education and the restrictive measures resulting from the pandemic. Fear and anxiety emerged as prevalent emotions. There was a significant worsening of the mental illness of students who already had a previous psychiatric diagnosis. Among the main stressing indices, the change in routine and withdrawal from the socio-affective network stood out. Economic issues involving even food insecurity situations were also mentioned. Most students negatively evaluated remote learning and pointed out several obstacles to the adaptation of this new system. They stated that receiving student aid during the pandemic positively influenced their permanence at university. As for the coping strategies adopted to respond to the challenges triggered by the pandemic, both the ones focused on the problem and the ones focused on emotion were included. Based on the results obtained, it is possible to conclude that the context of the pandemic and remote education had a negative impact on the experiences and mental health of students in socioeconomic vulnerability followed by the PNAES.